Medicines manufactured in pharmacies: features of validation of analytical methods and tests (Prior to the introduction of the monograph section of the SPU) - O. A. Yevtifieieva; V. A. Georgiyants (The State Expert Center of the Ministry of Health of Ukraine, 2021)
In most foreign countries, compounding medicines preparation are an important element of the pharmaceutical sector, the formulation of which is being distributed and developed taking into account the needs of today. Legal regulation of the circulation of these drugs is subject to the general requirements of the National Pharmacopoeia and the EuPh to SPhU but is carried out taking into account the characteristics of compounding medicines preparation: individual purpose, formulation, manufacture, quality control and implementation. In Ukraine, SPhU has monographs on various categories of compounding medicines preparation. But today there are some issues to ensure the quality control of compounding medicines preparation, which need to be consistent with the general requirements for medicines. The purpose of this work is to generalize the previously defined approaches and evaluate the results of their use in experimental studies on the development and validation of methods for quality control of compounding medicines preparation; substantiation and development of a fragment of the general monograph «Compounding medicines preparation» of SPhU. As a result of a critical analysis of the general requirements for validation of analysis methods and specifics of compounding medicines preparation, a standardized validation procedure was developed. When forming the tolerances of the content of individual ingredients in pharmaceutical dosage forms, the SPhU approach was chosen, that is the tolerances of the content at the level of ± 5%, ± 10%, ± 15% were chosen. Approbation of the standardized procedure for validation of methods for the quantitative determination of API in drugs manufactured in pharmacies was carried out on a significant number of names of about 50 compounding medicines preparation using spectrophotometric, photocolorimetric, refractometric and titrimetric methods of analysis. Studies have been conducted for different categories of drugs: concentrate solutions, semi-finished products, drugs made in stock, drugs made from finished drugs. The proposed standardized procedure for validation of analytical methods allows controlling of the quality of compounding medicines preparation in accordance with the requirements of the SPhU and avoids excessive costs. Based on the statistical analysis of experimental data, a draft part of the general monograph on compounding medicines preparation was formed: validation of analytical methods and tests.